Measuring susceptibility, infection, and recovery during the COVID-19 outbreak in Cambodia - Lim, Siphat; Leigh, Matthew Richard (International Journal of Innovative Research and Scientific Studies, 2025)
The SIR model is considered one of the most popular mathematical models used to measure the development of the COVID-19 pandemic. Three pieces of basic information susceptibility, infection, and recovery rates were needed to incorporate into the model's estimation parameters. Daily data from February 20, 2021, to August 20, 2021, were applied to calculate two key parameters: the contraction rate and the recovery rate. The solution from the ordinary differential equations showed that the effective contact and recovery rates were 0.0461 and 0.0061, respectively. Using the two parameters for simulation, the infection of COVID-19 reached its peak on July 2, 2022. Among the four main strategies employed by the government curfew, lockdown, vaccination, and stringency index measured based on school and workplace closures; restrictions on public gatherings; transport restrictions; and stay-at-home requirements in controlling the spread of the COVID-19 disease, the lockdown strategy played the most important role in reducing the daily number of infections of the disease, followed by curfew, stringency index, and vaccination.